Effect of rotating magnetic field on the fading effect of Al–5Ti–1B in commercial pure Al. Issue 15 (12th August 2014) - Chen, Hang; Jie, Jinchuan; Svynarenko, Kateryna; Ma, Hongjun; Li, Tingju
Abstract